2014
DOI: 10.1186/1471-2180-14-75
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics for mycobacterial peptidoglycan remodelling enzymes reveals extensive genetic multiplicity

Abstract: BackgroundMycobacteria comprise diverse species including non-pathogenic, environmental organisms, animal disease agents and human pathogens, notably Mycobacterium tuberculosis. Considering that the mycobacterial cell wall constitutes a significant barrier to drug penetration, the aim of this study was to conduct a comparative genomics analysis of the repertoire of enzymes involved in peptidoglycan (PG) remodelling to determine the potential of exploiting this area of bacterial metabolism for the discovery of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 104 publications
(130 reference statements)
1
54
0
Order By: Relevance
“…Recently, proteomic study has reported on the C.formosana-mediated down-regulated bacterial enzymes (triacylglycerol lipase, Nacetylmuramoyl-L-alanine amidase), upon exposure to C. formosana methanol extract(Yong et al., in press). The later amidase is especially noteworthy, as it was previously reported by others as a bacterial enzyme with functional role in the biosynthesis of peptidoglycans, an important building component in bacterial cell walls(Machowski et al, 2014). Nevertheless, further work is still needed to pinpoint which phytochemicals in the C. formosana extract are exactly responsible for this phenomenon.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Recently, proteomic study has reported on the C.formosana-mediated down-regulated bacterial enzymes (triacylglycerol lipase, Nacetylmuramoyl-L-alanine amidase), upon exposure to C. formosana methanol extract(Yong et al., in press). The later amidase is especially noteworthy, as it was previously reported by others as a bacterial enzyme with functional role in the biosynthesis of peptidoglycans, an important building component in bacterial cell walls(Machowski et al, 2014). Nevertheless, further work is still needed to pinpoint which phytochemicals in the C. formosana extract are exactly responsible for this phenomenon.…”
mentioning
confidence: 68%
“…Specifically, its rhodomyrtone (a xanthene derivative) was pinpointed as the potent phytochemical with anti-bacterial activity, parallel with inhibition potentials of commercial antibiotics. For instance, rhodomyrtone was reported with an MIC value of 0.39-0.78 µg/ml against MRSA strain, comparable to that of the commercial vancomycin (MIC: 1 25. …”
mentioning
confidence: 78%
See 1 more Smart Citation
“…The genome of M tuberculosis encodes many lytic enzymes, including at least five Resuscitation Promoting Factors (Rpfs) and greater than 10 peptidases and amidases in addition to penicillin binding proteins with potential lytic activities 24 . The Rpfs are most likely lytic transglycosylases with the product of RpfB having been recently confirmed as a GlcNAc-1,6-anhydroMurNAc disaccharide 25 .…”
Section: Resultsmentioning
confidence: 99%
“…In Mtb, Rpf represent inviting targets for intervention. They are important virulence factors, they lack human homologs ensuring a high degree of drug specificity and their extracellular nature means small molecule inhibitors do not need to enter the cell for biological activity (Kana et al, 2008;Machowski et al, 2014). Inhibitors of Rpf, such as 2-nitrophenylthiocyanates, could be given to patients with LTBI who need treatment with anti-TNFa inhibitors to prevent the reactivation of tuberculosis (Demina et al, 2009;Kaprelyants et al, 2012).…”
Section: Treatmentmentioning
confidence: 99%